Fifty Years of Work without Wages : Laborare est orare - Rowley, Charles, 1839-1933 (Place of publication not identified : publisher not identified, 1912)
Born in Ancoats, a deprived industrial area of Manchester, Charles Rowley (1839-1933) witnessed what he saw as the degeneration of inner-city life in the second half of the nineteenth century. His family's picture-framing business, combined with his love of culture, brought him into contact with the ideas and personalities associated with the Pre-Raphaelite Brotherhood, notably William Morris. As a social reformer, Rowley was suspicious of organised charity and its tendency to patronise those it tried to support. Through a number of progressive initiatives, he laboured to bring art and culture to working people: the Ancoats Brotherhood, which organised lectures and reading groups, was among the many projects he fostered. First published in 1911, these well-illustrated memoirs present a thoughtful portrait of Rowley's experiences and enthusiasms, touching upon his interactions with such artists as Ford Madox Brown, Dante Gabriel Rossetti and William Holman Hunt.
Keywords: Ancoats Brotherhood; Art -- England; Pre-Raphaelitism -- England; Manchester (England) -- Social conditions